Synthesis of antibacterial 1,3-diyne-linked peptoids from an Ugi-4CR/Glaser coupling approach - Brauer, Martin C. N.; Neves Filho, Ricardo A. W.; Westermann, Bernhard; Heinke, Ramona; Wessjohann, Ludger A. (Beilstein Journal of Organic Chemistry, 2015)
A library of ten 1,3-diyne-linked peptoids has been synthesized through an Ugi four-component reaction (U-4CR) followed by a copper-catalysed alkyne homocoupling (Glaser reaction). The short and chemoselective reaction sequence allows generating diverse (pseudo) dimeric peptoids. A combinatorial version allows the one-pot preparation of, e.g., six-compound-libraries of homo- and heterodimers verified by ESI-MS and HPLC. In a preliminary evaluation, some compounds display moderate activity against the Gram-positive bacterium Bacillus subtilis.
Keywords: antibacterial; combinatorial; diynes; homodimerization; multicomponent reactions; peptoids; Ugi reaction